Efficient eco-friendly composite fluorine anhydrite-based materials - Yakovlev, Grigory; Keriene, Jadvyga; Gordina, Anastasiia; Polyanskikh, Irina; Bekmansurov, Milan (International Conference “Environmental Engineering”, 2017)
The paper presents possible ways of utilizing technogenic waste – fluorine anhydrite – by its use in production of dry mortars and piece goods from lightweight concrete with expanded polystyrene, as a organic filler, for lowrise construction. The developed dry mortars are based on fluorine anhydrite binder and complex modifier comprising curing activator (sulfate or alkaline) and finely dispersed additive. The fluorine anhydritebased compositions have improved physical and performance characteristics, including the improved strength and average density and reduced water absorption compared to the control composition. The developed lightweight anhydrite polystyrene concrete has the density grade of 700 kg/m3 and good vapor and gas permeability. The concrete is stabile while using and fire safe, because each granule of expanded poly styrene is coated with anhydrite matrix, and has the strength sufficient for structural and heat insulating slabs and blocks. All mentioned compositions are ecofriendly and are in great demand for lowrise construction. Therefore the manufacturing of these compositions will consume a large amount of technogenic waste and will reduce the environmental load on the region where the waste is located.